Institucionalização cognitiva e social da Organização e Representação do Conhecimento na Ciência da Informação no Brasil - Martins, Gracy Kelli [UNESP] (2014)
The knowledge organization and representation (KOR) have epistemological roots in ancient times. It is among the concerns of human affairs, from ancient civilizations. Their processes were taken as art, technique to transform itself into a scientific discipline. Today, lies at the core of Information Science (IS) and directs much of its theoretical and instrumental research. In Brazilian IS is nominated by the expression Knowledge Organisation and Representation, considering that even being considered a subdiscipline, it also represents an independent research field that permeates other scientific areas. As a subdiscipline of IS interest here investigate its scientific institutionalization in cognitive and social context. To evaluate the institutionalization of a scientific field, it is necessary to measure: developed processes; degree of coherence; clarity of the theoretical and methodological framework; conceptual framework; actions organization by disseminating results; and the relationship between its researchers. As elucidation to the problem, this research was guided by the following research question: is KOR, in Information Science in Brazil, cognitively and socially institutionalized? To answer this question, the following objectives were set: to identify the levels of social institutionalization, from the evaluation of the research lines in postgraduate programs in IS, the research groups registered in the CNPq Directory and specialized events in KOR in Brazil, and measure the levels of cognitive institutionalization from the specialized scientific literature and intellectual identity of its researchers. The selected universe for the investigation of cognitive institutionalization is formed up of papers published in specialized areas such as the annals of the GT2 from ENANCIB (1994-2013) and the ISKO-Brazil (2011-2013). The clipping focused on the most productive authors possessing publications in 50% or more of the issues of...